Mitochondrial Mechanisms of Metabolic Reprogramming in Proliferating Cells - Ines Sousa, Maria; Sofia Rodrigues, Ana; Pereira, Sandro; Perestrelo, Tania; Correia, Marcelo; Ramalho-Santos, Joao (Current Medicinal Chemistry, 2015)
Mitochondria are responsible for coordinating cellular energy production in the vast majority of somatic cells, and every cell type in a specific state can have a distinct metabolic signature. The metabolic requirements of cells from different tissues changes as they proliferate/differentiate, and cellular metabolism must match these demands. Proliferating cells, namely cancer cells and stem cells, tend to prefer glycolysis rather than a more oxidative metabolism. This preference has been exploited for the improvement of new biotechnological and therapeutic applications. In this review, we describe mitochondrial dynamics and energy metabolism modulation during nuclear reprogramming of somatic cells, which will be essential for the development and optimization of new protocols for regenerative medicine, disease modeling and toxicological screens involving patientspecific reprogrammed cells.
Keywords: pluripotency